2013
DOI: 10.1371/journal.ppat.1003582
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis of In Vitro and In Vivo Genetic Fitness of Pseudomonas aeruginosa Using High-Throughput Sequencing of Transposon Libraries

Abstract: High-throughput sequencing of transposon (Tn) libraries created within entire genomes identifies and quantifies the contribution of individual genes and operons to the fitness of organisms in different environments. We used insertion-sequencing (INSeq) to analyze the contribution to fitness of all non-essential genes in the chromosome of Pseudomonas aeruginosa strain PA14 based on a library of ∼300,000 individual Tn insertions. In vitro growth in LB provided a baseline for comparison with the survival of the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
197
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(210 citation statements)
references
References 51 publications
8
197
1
1
Order By: Relevance
“…Both paYieF and paArsH have also been shown to be required for systemic infection in mice by P. aeruginosa PA14 [12]. This data supports the hypothesis that azoreductases are required for bacterial pathogenicity.…”
Section: Flavin Cofactor Selectivitysupporting
confidence: 75%
See 2 more Smart Citations
“…Both paYieF and paArsH have also been shown to be required for systemic infection in mice by P. aeruginosa PA14 [12]. This data supports the hypothesis that azoreductases are required for bacterial pathogenicity.…”
Section: Flavin Cofactor Selectivitysupporting
confidence: 75%
“…Studies in Pseudomonas aeruginosa using single gene deletion mutants have shown that azoreductase 1 (paAzoR1) is required for systemic infection of mice by a clinical strain of P. aeruginosa [11]. In addition both paAzoR1 and azoreductase 2 (paAzoR2) are required for systemic infection of mice by P. aeruginosa PA14 [12]. Taken as a whole, this data suggests a role for azoreductases in bacterial pathogenicity.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Direct experimental approaches are not feasible for human gut symbionts, but rodent models have been used with considerable success (2-7). Several pathogens have been examined using Tn-seq in vivo, within different tissue types (38,(41)(42)(43). Some critical mechanisms for S. alvi colonization of the bee gut, including LPS modifications, membrane integrity components, the stringent response, proteases, and DNA break repair, are also important for infection by human pathogens (41)(42)(43).…”
Section: Resultsmentioning
confidence: 99%
“…Several pathogens have been examined using Tn-seq in vivo, within different tissue types (38,(41)(42)(43). Some critical mechanisms for S. alvi colonization of the bee gut, including LPS modifications, membrane integrity components, the stringent response, proteases, and DNA break repair, are also important for infection by human pathogens (41)(42)(43). Similarly, colonization of light-producing organs by the squid symbiont Vibrio fisheri depends on genes dictating biofilm formation and cellular stress responses (44).…”
Section: Resultsmentioning
confidence: 99%